Transition expectations, motivation, engagement and sense of belonging of pupils in secondary school. A quantitative approach - Γκανούδη Κλεοπάτρα-Μαρία (Education Sciences, 2025)
This paper presents the quantitative results of the comparison of general class students and those who receive Special Education services in the 1st High School, regarding the dimensions a) transition expectations b) learning motivation, c) active involvement in the learning process and d) of the feeling of "belonging". It seeks to cover the research gap, regarding the measurement of the above variables, both in the international and Greek literature. In the present research, quantitative data were collected from N=420 1st High School students, through three psychometric tools. To measure transition expectations, the self-report questionnaire “The Impending Transition to Secondary School Perceived as a Challenge and Threat”, learning motivation and active involvement in the learning process, the “The Student Motivation and Engagement Scale-High” scale was administered School" and the feeling of "belonging", the "Inclusion Climate Scale". Omega reliability indices of the administered instruments were also tested. In the results, gender differences were identified in five of their subscales. The two genders differed significantly on learning motivation and active involvement in the learning process, learning focus, schoolwork management, stress levels, uncertain control, and academic threat. No statistically significant differences were found between typically developing students and those with Special Educational Needs.